Implikasi Kompensasi dalam Meningkatkan Motivasi dan Prestasi Kerja Tenaga Pendidik di Lembaga Pendidikan - Prasetyo, Muhammad Doni; Rindaningsih, Ida (TSAQOFAH, 2025)
The decline in motivation and achievement of educators in an educational institution due to the nominal amount of salary is not in accordance with the work that has been done. therefore, compensation is present to increase the motivation and achievement of educators. both in material and non-material forms. in addition, an approach is also taken to provide a sense of satisfaction to educators regardless of the nominal compensation that has been given. using the Systematic Literature Review method, where researchers analyze several research journals that have a relationship with the theme that has been determined. then present it in the form of data and draw conclusions with the appropriate data that has been presented. compensation has a high role in increasing the motivation of educators. in addition, compensation has a significant influence on work performance. Compensation and rewards have a significant influence on increasing motivation and work performance of educators and education personnel. Compensation and rewards have a significant influence on increasing the motivation and work performance of educators and education personnel. When the nominal amount of compensation is deemed not quite appropriate, the Foundation or the head of the Educational Institution can increase it with incentives outside the amount of monthly compensation.